An online health status report to support public health in Belgium. (13th November 2019) - Scohy, A; Devleesschauwer, B; Renard, F
Abstract: Issue: Monitoring population health is crucial for policymakers. In Belgium, health monitoring only existed at regional level, with no integrated view at country level. Policy/tool: The Health Status Report (HSR) project developed a tool for centralizing key health indicators. The HSR aims to support policymakers in multiple ways: as a 'warning signal', by contributing to the planning of health policies, and as an assessment tool for those policies. Rather than being exhaustive, the HSR selects key indicators to highlight important needs. These indicators have been identified through literature and consultations with experts and stakeholders. Topics include life and health expectancies, mortality, morbidity, and lifestyles, with an important focus on socioeconomic inequalities. Good results and health gaps are underlined with international comparisons, trend analyses, and comparisons with reference values. By disaggregating the data by sex, age, geographic level or socio-economic level, specific health needs are identified. Results: The main outcome of the project is a continuously updated website: www.healthybelgium.be . The report highlighted that, although the Belgian health status is rather good, there is room for improvement: for some indicators Belgium lags behind other European countries; regional disparities remain important, with most indicators revealing a better health status in Flanders than in Brussels and Wallonia. Socioeconomic disparities also remain very important, and for some indicators even tend to worsen. Comparing the Belgian health status to that of the EU-15 results in more severe conclusions than in international reports. Conclusions: We developed a new tool to support public health policy in Belgium through benchmarking and trend and disparity analyses of several health indicators. The tool will be expanded in the next years, integrating for instance the results of the Belgian national burden of disease study. Key messages: We developed an online health status monitoring tool to inform policymakers. The rather good health status hides important regional and socioeconomic disparities in Belgium.